When Did Coloring Books Become Mindful? Exploring the Effectiveness of a Novel Method of Mindfulness-Guided Instructions for Coloring Books to Increase Mindfulness and Decrease Anxiety - Mantzios, Michail; Giannou, Kyriaki (Frontiers in Psychology, 2018)
Mindfulness has been associated with the use of colouring books for adults; however, the question of whether they increase mindfulness has not been addressed. In two studies, we examined whether mindfulness is increased through colouring books, and whether ongoing guidance while colouring is necessary, to imitate mindfulness meditation. In the first randomized controlled experiment, university students (n = 88) were assigned to an unguided mandala colouring group (i.e., described in mainstream literature as a mindfulness practice) or to a free-drawing group. Measurements of state mindfulness and state anxiety were taken pre- and post- experiment. Results indicated no change in mindfulness or anxiety. In the second randomized controlled experiment, university students (n = 72) were assigned to an unguided mandala colouring group (i.e., same as Experiment 1), or, to a mindfulness-guided colouring group (i.e., same as the unguided colouring group with a mindfulness practitioner guiding participants as in mindfulness breathing meditation, with instructions modified and applied to colouring). Results indicated that the mindfulness-guided mandala colouring group performed better in decreasing anxiety, but no change was observed in mindfulness. Exit interviews revealed that some participants did not like the voice guiding them while colouring, which suggested further differing and significant findings. While mindfulness-guided colouring appear promising, guidance or instructions on how to colour mindfully may require further development and adjustment to enhance health and wellbeing.